The association of fluoride in the treatment of incipient caries lesions - Salgado, Vinícius Esteves (2010)
The caries disease, when diagnosed in its initial stage, can be treated in a non-invasively way through remineralizating agents, such as fluorides. Among the fluoridated compounds, dentifricies are the highlights, the most cost-effective due to convenience, low cost and frequency of application. However, in high-risk patients and/or caries activity, the fluoridated products association can bring additional benefits. The purpose of this study was to conduct a survey of the literature on the advantages and disadvantages of fluoridated products association in the remineralizating treatment of incipient caries lesions.